2015
DOI: 10.1080/14616688.2015.1065509
|View full text |Cite
|
Sign up to set email alerts
|

Towards a gendered political economy of water and tourism

Abstract: In many holiday destinations, the tourism industry exerts an enormous strain on water supplies. This generates a range of social problems, not least because local inhabitants often have to compete with the tourism sector over the access, allocation and use of water for their personal and domestic needs. Nevertheless, there has been very little academic research on the link between tourism and the impact of water scarcity on destination populations in developing countries. While there is a wealth of literature … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0
7

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 56 publications
0
26
0
7
Order By: Relevance
“…In much of the world, women are the primary household water managers (Cole & Ferguson, ; Sultana & Loftus, ), just as they are often the primary preparers of food (Wutich & Brewis, ). A recent meta‐analysis of 42 studies found that there is moderate quantitative evidence and strong qualitative evidence to demonstrate that carrying water heightens fatigue and other physical ailments (Geere et al, ; Geere, Cortobius, Geere, Hammer, & Hunter, ).…”
Section: How Might Household Water Insecurity Exacerbate Food Insecurmentioning
confidence: 99%
“…In much of the world, women are the primary household water managers (Cole & Ferguson, ; Sultana & Loftus, ), just as they are often the primary preparers of food (Wutich & Brewis, ). A recent meta‐analysis of 42 studies found that there is moderate quantitative evidence and strong qualitative evidence to demonstrate that carrying water heightens fatigue and other physical ailments (Geere et al, ; Geere, Cortobius, Geere, Hammer, & Hunter, ).…”
Section: How Might Household Water Insecurity Exacerbate Food Insecurmentioning
confidence: 99%
“…Their use is associated with leisure activities in Western societies (Van Leeuwen 1999;Wiltse 2007;Wolf and Hof 2013), and pools have become a common element in the sprawling areas of many cities (Salvati et al 2015). Pools in the richer world, especially, constitute part of the myriad of artefacts associated with suburban environments and the landscapes of "high-carbon lives" of residential and tourist settings (Leichenko and Solecki 2005;Urry 2011;Cole and Ferguson 2015).…”
Section: 水资源。mentioning
confidence: 99%
“…In particular when fresh water is scarce, does the issue of access become particularly significant as it is paramount for sustainable livelihoods. Following from previous research on inequitable and unsustainable water distribution due to the expression of social power linked to the political ecology of scarce resources (See Cole, 2012), Cole and Ferguson (2015) focus on the relation between the importance of gender in social reproduction practices (responsibility for water in households), class and migration. In their contribution, they highlight the gendered division of labour as social structure framing the relationship between households and water, but they also underline how the gendered responsibility for social reproduction is used to resist and challenge the existing political economy of water use by the tourism industry.…”
Section: Introductionmentioning
confidence: 99%